TACIT KNOWLEDGE: REVISITING THE EPISTEMOLOGY OF KNOWLEDGE - Lejeune, Michel (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
ABSTRACT. The concept of tacit knowledge encompasses all of the intricacy of the different experiences that people acquire over time, and which they utilize and bring to bear in carrying out tasks effectively, reacting to unforeseen circumstances, or innovating. The intuitive nature of tacit knowledge, its particular context, and the difficulty of expressing it in words call into question the very foundation of the notion of competency and its value in education. What parameters might be used to clarify tacit knowledge and its place within so-called “organizational” knowledge? Certain characteristics of tacit knowledge may contribute new considerations to the ongoing debate as to the true nature of competency. LE SAVOIR TACITE: REVISITER L'ÉPISTÉMOLOGIE DES SAVOIRS RÉSUMÉ. La notion de savoir tacite implique toute la richesse de l’expérience qu’une personne acquiert avec le temps, qu’elle mobilise et qu’elle met en œuvre dans le but d’accomplir efficacement une tâche, de réagir à des imprévus ou d’innover. Le caractère intuitif du savoir tacite, son contexte particulier et la difficulté à l’exprimer en mots interrogent les fondements mêmes de la notion de compétence et sa valeur pour l’éducation. Que seraient les paramètres pouvant nous aider à préciser le savoir tacite et sa place dans l’ensemble du savoir dit “organisationnel” ? Certaines caractéristiques du savoir tacite peuvent apporter de nouveaux éléments au présent débat quant à la véritable nature de la compétence.